An innovative approach to manufacturing flexible decorative wood veneer using EVA film as adhesive and reinforcing materials. Issue 2 (4th March 2023) - Zhang, Xinhao; Fang, Lu; Zhang, Yu; He, Ye; Lu, Yuxin; Yu, Jiayan
ABSTRACT: In order to solve the problems of easy cracking and poor flexibility of decorative wood veneer, a simple and efficient approach to manufacturing flexible decorative wood veneer was proposed. Ethylene-vinyl acetate (EVA) film was used as adhesive and reinforcing material for developing EVA film reinforced decorative wood veneer (EVA-RDV). The results showed that EVA film and Manchurian Ash decorative wood veneer could be well composited at 110 °C without special treatment. The flexibility was maintained at 4 ∼ 6 mm and the transverse tensile strength was 0.99 MPa, which was 412.5% higher than that of the original decorative veneer (DV). It was found that EVA film had better adaptability of veneer moisture content (MC). The cavity proportion was kept within 5%, and the flexibility was little affected. The surface bonding strength was maintained at a stable state of 0.8 ∼ 1 MPa (higher than the standard 0.4 MPa). Only 100 °C was needed to complete the surface decoration, and the optimal surface bonding strength reached 1.17 MPa. The water resistance of all decorative veneered Medium Density Fiberboards (MDF) met the requirements of indoor use in GB/T 15104-2006.